Aldose reductase inhibitors and nanodelivery of diabetic therapeutics - Prior, Allan M.; Thapa, Mahendra; Hua, Duy H. (My University, 2012)
Nanotechnology is a rapidly emerging drug-delivery system that makes possible the controlled release of small molecules, and nanodelivery of therapeutic molecules using nanoparticles or nanogels represents a major improvement for more focused delivery of such therapeutic molecules. The delivery of insulin for the control of diabetes mellitus (DM) and aldose reductase inhibitor (ARI) for diabetic complications may provide better treatment of diabetes. A structural overview of aldose reductase including computational docking experiments with HAR-1, various ARIs, aldose-keto reductase, and nanodelivery of insulin, ARI’s, and drug molecules are described.
Citation: Prior, A.M., Thapa, M., & Hua, D.H. (2012). Aldose reductase inhibitors and nanodelivery of diabetic therapeutics. Mini-Reviews in Medicinal Chemistry, 12(4), 326- 336.
Keywords: Aldose reductase; Aldose reductase inhibitors; Aldo-keto reductase; Diabetes; Insulin; Nanodelivery; Nanogels; Tricyclic pyrone molecules